Bacterial biofilm composition in healthy subjects with and without caries experience. Issue 1 (1st January 2019) - Schoilew, Kyrill; Ueffing, Helena; Dalpke, Alexander; Wolff, Björn; Frese, Cornelia; Wolff, Diana; Boutin, Sébastien
ABSTRACT: Objective: The composition of the oral microbiome differs distinctively between subjects with and without active caries. Still, caries research has mainly been focused on states of disease; aspects about how biofilm composition and structure maintain oral health still remain widely unclear. Therefore, the aim of the study was to compare the healthy oral microbiome of caries-free adult subjects with and without former caries experience using next generation sequencing methods. Methods: 46 samples were collected from subjects without any signs of untreated active caries. Samples of pooled supragingival plaque from 19 subjects without caries experience (NH; DMFT = 0) and 27 subjects with 'caries experience' ( CE; DMFT > 0 [F(T)> 0; D(T)= 0]) were analyzed by 16S ribosomal RNA amplicon sequencing. Results: Subjects with caries experience did not exhibit a dramatically modified supragingival plaque microbiome. However, we observed a slight and significant modification between the two groups, validated by PERMANOVA ( NH vs. CE: R2 0.04; p= 0.039). The composition of the microbiome of subjects with caries experience indicates a tendency to lower α-diversity and richness. Subjects without caries experience showed a significant higher evenness compared to patients with previous caries. LDA effect size (LEfSe) analysis demonstrated that the genus Haemophilus is significantly more frequent in patients with caries experience. For the group without caries experience LefSe analysis showed a set of 11 genera being significantly more frequent, including Corynebacterium, Fusobacterium, Capnocytophaga, Porphyromonas, Prevotella, and Leptotrichia. Conclusion: The analysis of the oral microbiome of subjects with and without caries experience indicates specific differences. With the presence of Corynebacterium and Fusobacterium subjects without caries experience exhibited more frequently organisms that are considered to be main actors in structural plaque formation and integration. The abundance of Corynebacterium might be interpreted as a signature for dental health.